2016
DOI: 10.1007/s13361-016-1544-4
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Metabolite Biomarkers for Soft Tissue Sarcomas Discovered by Mass Spectrometry Imaging

Abstract: Metabolites can be an important read-out of disease. The identification and validation of biomarkers in the cancer metabolome that can stratify high-risk patients is one of the main current research aspects. Mass spectrometry has become the technique of choice for metabolomics studies, and mass spectrometry imaging (MSI) enables their visualization in patient tissues. In this study, we used MSI to identify prognostic metabolite biomarkers in high grade sarcomas; 33 high grade sarcoma patients, comprising osteo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 44 publications
1
33
0
Order By: Relevance
“…Interestingly, some of the metabolites involved, such as tryptophan, succinate or 2-hydroxyglutarate, are key features of metabolic rewiring, which in turn is a crucial aspect of leukemogenesis. L-carnitine, responsible for fatty acid transportation across the mitochondrial membrane, was considerably higher in FLT3-ITD, a result which is in line with other reports on different types of cancer and that indicates carnitine as a potential useful biomarker in pediatric AML with FLT3-ITD [67,68].…”
Section: From Cytogenetic Aberrations To Metabolic Responsesupporting
confidence: 90%
“…Interestingly, some of the metabolites involved, such as tryptophan, succinate or 2-hydroxyglutarate, are key features of metabolic rewiring, which in turn is a crucial aspect of leukemogenesis. L-carnitine, responsible for fatty acid transportation across the mitochondrial membrane, was considerably higher in FLT3-ITD, a result which is in line with other reports on different types of cancer and that indicates carnitine as a potential useful biomarker in pediatric AML with FLT3-ITD [67,68].…”
Section: From Cytogenetic Aberrations To Metabolic Responsesupporting
confidence: 90%
“…Serum profiling had previously shown a similar increase in carnitine abundance for patients with non-small-cell lung cancer as compared to healthy controls 25 . In addition, a recent metabolomics study reported increased carnitine levels with poor metastasis free survival outcomes in patients with different forms of soft tissue sarcoma 26 . These data suggests carnitine as a common thread among several cancer metabolomics studies, and our results further indicate that carnitine might be a useful target in future biomarker studies for FLT3-ITD pediatric AML.…”
Section: Discussionmentioning
confidence: 99%
“…In current practice, canine sarcomas are diagnosed using human guidelines hence the diagnostic procedures face similar challenges. MS imaging (MSI) has already been demonstrated to provide excellent prognostic information on this group of diseases (Lou et al, 2017).…”
Section: Significancementioning
confidence: 99%